2010
DOI: 10.1055/s-0030-1267474
|View full text |Cite
|
Sign up to set email alerts
|

Results of Surgical Treatment of Unresolved Osgood-Schlatter Disease in Adults

Abstract: Osgood-Schlatter is a common disease with most cases resolving spontaneously with skeletal maturity. Adults with continued symptoms may need surgical treatment if they fail to respond to conservative measures. The purpose of this study is to describe the pathological lesions, our surgical technique, and the results of our surgical treatment of Osgood Schlatter disease in adults. Thirty-five adult patients (37 knees) had surgery for unresolved Osgood-Schlatter disease. Three patients were lost for follow-up. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…[7][8][9]13 Modifications with an anterolateral incision and reflection of the patellar tendon have been proposed to reduce this risk. 5 Endoscopic approaches have been reported with the advantage of avoidance of painful surgical scars because the portal incisions are located away from the patellar tendon. 4 Sports activity may be allowed earlier because the patellar tendon is not violated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9]13 Modifications with an anterolateral incision and reflection of the patellar tendon have been proposed to reduce this risk. 5 Endoscopic approaches have been reported with the advantage of avoidance of painful surgical scars because the portal incisions are located away from the patellar tendon. 4 Sports activity may be allowed earlier because the patellar tendon is not violated.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical options include excision of the ossicle together with reduction osteotomy or debridement of the tibial tuberosity, drilling of the tubercle, autogenous bone peg insertion through the tubercle, or sequestrectomy (i.e., excision of the ununited ossicles and free cartilaginous pieces). [3][4][5][6][7][8][9] These are usually performed as open procedures. Recently, endoscopic resection of the ossicle and debridement of the tibial tuberosity have been reported.…”
mentioning
confidence: 99%
“…Despite that favorable natural progress has been recognized as a self-limiting disease in 90% of the patients, severe pain in the tibial tuberosity and difficulties in daily life are often complained by athletes or military personnel who frequently perform activities that cause stress on the knee joint regardless of the completion of the growth 2) . Various treatment methods including surgical treatment have been performed for the patients with severe symptoms refractory to conservative treatment 2 3 4 5 6 7 8) ; however, cases where the symptoms persist even after surgical treatment have often been reported 3 4 9 10 11 12) . This has been thought to be due to the lack of research on pathophysiology and clinical progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 An ossicle may impinge on the patellar tendon, causing long-term impairment of kneeling or running. 4 However, a sequential MRI study of adolescents with symptomatic OSD revealed 100% with patellar tendon pathology and only 32% with ossicle formation. 5 Improvement in patellar tendinosis was demonstrated in those that became asymptomatic, despite persistence of nonunion ossicles.…”
mentioning
confidence: 99%